Non-Darcy natural convection flow for non-Newtonian nanofluid over cone saturated in porous medium with uniform heat and volume fraction fluxes. Issue 2 (2nd March 2015) - Chamkha, A; Abbasbandy, S; Rashad, A.M.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effect of uniform lateral mass flux on non-Darcy natural convection of non-Newtonian fluid along a vertical cone embedded in a porous medium filled with a nanofluid. Design/methodology/approach – The resulting governing equations are non-dimensionalized and transformed into a non-similar form and then solved numerically by Keller box finite-difference method. Findings – A comparison with previously published works is performed and excellent agreement is obtained. Research limitations/implications – The model used for the nanofluid incorporates the effects of Brownian motion and thermophoresis. It is assumed that the cone surface is preamble for possible nanofluid wall suction/injection, under the condition of uniform heat and nanoparticles volume fraction fluxes. Originality/value – The effects of nanofluid parameters, Ergun number, surface mass flux and viscosity index are investigated on the velocity, temperature, and volume fraction profiles as well as the local Nusselt and Sherwood numbers.